Front cover: GPCR6A Is a Molecular Target for the Natural Products Gallate and EGCG in Green Tea. Issue 8 (24th April 2018) - Pi, Min; Kapoor, Karan; Ye, Ruisong; Smith, Jeremy C.; Baudry, Jerome; Quarles, Leigh D.
Abstract : Mol. Nutr. Food Res. 2018, 62, 1700770 DOI:10.1002/mnfr.201700770 The cover image depicts the superimposition of transmembrane and Venus flytrap models of GPRC6A (orange). Two small molecule effectors of GPRC6A are shown (in purple) in both the transmembrane and Venus fly trap domains, in locations predicted by computational modeling. Further details can be found in article number1700770 by Min Pi, Leigh D. Quarles, and co‐workers.